Determinan Perilaku Wisatawan terhadap Kualitas Pengalaman Wisata dan Willingness to Pay (WTP) Wisatawan pada DTW Pura Uluwatu - Ni Putu Siska Wulandari; Made Sinthya Aryasthini Mahaendrayasa (Trending: Jurnal Manajemen dan Ekonomi, 2026)
This research is driven by the phenomenon of Uluwatu Temple’s management as a leading cultural tourism destination facing ticket price increase policies amidst regional infrastructure development. This study aims to analyze the determinants affecting tourist experience quality and Willingness to Pay, including price perception, destination image, and income level, while also testing the mediating role of tourist experience quality. Using a quantitative approach, the study was conducted at Uluwatu Temple with 100 domestic tourist respondents selected through purposive sampling. Data were analyzed using path analysis and the Sobel test. The results indicate that destination image and income have a positive and significant effect on tourist experience quality, while price perception was found to have no significant effect. In the second model, destination image, income, and tourist experience quality significantly influence Willingness to Pay. The analysis reveals that destination image is the most dominant determinant influencing tourist experience quality, while tourist experience quality serves as the most dominant factor in determining tourists' Willingness to Pay. Furthermore, the mediation test confirms that tourist experience quality significantly mediates the influence of destination image on Willingness to Pay. The implications of this study emphasize that management should focus on strengthening destination image as the primary decisive factor to increase tourists' financial support through their Willingness to Pay for the sustainability of temple conservation.